1980
DOI: 10.1017/s030500090000283x
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of some Dutch morphological rules

Abstract: The acquisition of the morphological rules for plural, agentive, and diminutive suffixes in Dutch was studied. Subjects included 7- and 12-year-old native speakers, and second-language learners in three age groups (5–10 years, 12–18 years, and adult). The first- and second-language learners showed very similar orders of acquisition for the rule systems governing plural and diminutive, but the second-language learners showed a subtle form of interference from their first language in acquiring the agentive. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…Note that they also found /ətjə/ to be less productive than initially expected even in adults. More recently Peelaerts (2008) confirmed the findings from the Snow et al (1979) and Den Os and Harder (1987) studies. She tested four-to ten-year-old children and also found that the lower the type frequency of the allomorph, the later it was acquired.…”
Section: The Dutch Diminutivementioning
confidence: 58%
See 2 more Smart Citations
“…Note that they also found /ətjə/ to be less productive than initially expected even in adults. More recently Peelaerts (2008) confirmed the findings from the Snow et al (1979) and Den Os and Harder (1987) studies. She tested four-to ten-year-old children and also found that the lower the type frequency of the allomorph, the later it was acquired.…”
Section: The Dutch Diminutivementioning
confidence: 58%
“…In the case of the English past tense, the /Id/ allomorph has the lowest type frequency and is also the least productive (Blom & Paradis, 2013;Blom et al, 2012;Marchman, 1997;Matthews & Theakston, 2006;Tomas et al, 2017a). As will be elaborated on in the next section, the few studies that have investigated the Dutch diminutive have also found that type frequencies of the different diminutive allomorphs affected production accuracies (Den Os & Harder, 1987;Peelaerts, 2008;Snow, Smith, & Hoefnagel-Höhle, 1979). In contrast, Rispens and de Bree (2014) did not find an effect of type frequency on production accuracies of the Dutch past tense in TD children and children with language impairment.…”
Section: The Acquisition Of Morphophonological Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, more recent research provided ample evidence that, in fact, both plural forms of Dutch should be considered regular (Baayen, Dijkstra, & Schreuder, 1997;Baayen et al, 2002;Keuleers et al, 2007;Van Wijk, 2002): clippings, nonce words, acronyms, onomatopoeic terms, proper names, and unassimilated borrowings may take -s or -en as the plural affix, depending on the phonological environment (particularly with regard to stress and sonority) created by the singular form. For instance, when participants in a study by Snow, Smith, and Hoefnagel-Höhle (1980) were asked to produce the plural of nonce words (e.g. flik, hinden), they used the phonologically appropriate affix ( flikken, hindens).…”
Section: Morphological Complexity Of the Languagementioning
confidence: 99%
“…(1) new words AE kepsen, flonkers (Snow et al, 1980) loanwords AE fezzen, ciabatta's acronyms AE HATten, PABOs (Baayen et al, to appear) names AE de van Wijken, de van Dijks If it turns out that Dutch has two default affixes, however, this is problematic for the dual model. The central criterion for the default in this model is the ability to attach to a stem without morphological or phonological conditions.…”
mentioning
confidence: 99%